Current trends of practical issues concerning micropapillary thyroid carcinoma: The Korean Society of Thyroid-Head and Neck Surgery. Issue 45 (November 2017) - Lee, Yoon Se; Lee, Byung-Joo; Hong, Hyun Joon; Lee, Kang-Dae
Abstract : Abstract: Although several thyroid associations have published various guidelines, controversies especially in cases of micropapillary thyroid cancer (MPTC) still exist. This survey was designed to collect information about diagnostic tests and treatments performed on patients with MPTC and help identify current trends in thyroid surgery. We developed questionnaires about the management methods for MPTC, which were used to identify factors related to indications of fine needle aspiration (FNA), type of surgery, and central lymph node dissection (CLND). Active 60 members of the Korean Society of Thyroid-Head and Neck Surgery participated in the study in September 2016. Ultrasound-guided FNA was usually initiated when the tumor was at least 5 mm (60%). All respondents preferred ultrasound-guided FNA and surgery for nodules with extrathyroidal extension (ETE). The preferred treatment option for intraglandular MPTC was lobectomy (92%) rather than active surveillance (8%). Posterolateral ETE increased the respondents' preference for total thyroidectomy (61.7%). Active surveillance was preferred for tumors <5 mm, which was decreased by the presence of ETE. The presence of ETE (73.3%) and its proximity to critical organs (46.7%) were the main determining factors for prophylactic CLND. For multiple metastatic lymph nodes at level III, selective neck dissection including levels IIb (23.3%) and V (78.3%) was preferred in addition to levels IIa, III, VI, and V. Korean head and neck surgeons favored total thyroidectomy and CLND in cases wherein ETE, central lymph node metastasis, or critical organ involvement was suspected.